Construction of Benzosultam‐Containing Fused‐ and Linked‐Biheterocycles by a Cascade Double Nucleophilic Cyclization. Issue 10 (8th March 2022) - Das, Jonali; Borah, Biraj Jyoti; Das, Sajal Kumar
Abstract: Although nucleophilic aromatic substitution (SN Ar) and many nucleophilic epoxide ring‐opening reactions proceed under similar anionic conditions, the literature examples of using these reactions in tandem for the construction of heterocyclic compounds are scarce. In this article, we disclose a detailed account of the synthesis of benzothiaoxazepine‐1, 1‐dioxide‐containing fused‐ and linked‐biheterocycles by a base‐mediated, exo ‐selective intramolecular epoxide‐opening/intramolecular nucleophilic aromatic substitution cascade of epoxide‐tethered ortho ‐fluorobenzenesulfonamides. A wide range of substrates exhibited high overall yields and complete regio‐ and diastereoselectivity Abstract : Benzothiaoxazepine‐1, 1‐dioxide‐containing fused‐ and linked‐biheterocycles have been synthesized in diastereoselective fashion by a NaH‐mediated, exo ‐selective intramolecular epoxide‐opening/SN Ar cascade of epoxide‐tethered ortho ‐fluorobenzenesulfonamides.